Investigating the Feasibility of Child Mortality Surveillance With Postmortem Tissue Sampling: Generating Constructs and Variables to Strengthen Validity and Reliability in Qualitative Research. (9th October 2019) - O'Mara Sage, Elizabeth; Munguambe, Khátia R; Blevins, John; Guilaze, Rui; Kosia, Baindu; Maixenchs, Maria; Bassat, Quique; Mandomando, Inácio; Kaiser, Reinhard; Kone, Ahoua; Jambai, Amara; Myburgh, Nellie D; et al.
Abstract: Background: The Child Health and Mortality Prevention Surveillance (CHAMPS) network aims to generate reliable data on the causes of death among children aged <5 years using all available information, including minimally invasive tissue sampling (MITS). The sensitive nature of MITS inevitably evokes religious, cultural, and ethical questions influencing the feasibility and sustainability of CHAMPS. Methods: Due to limited behavioral studies related to child MITS, we developed an innovative qualitative methodology to determine the barriers, facilitators, and other factors that affect the implementation and sustainability of CHAMPS surveillance across 7 diverse locations in sub-Saharan Africa and South Asia. We employed a multimethod grounded theory approach and analytical structure based on culturally specific conceptual frameworks. The methodology guided data interpretation and collective analyses confirming how to define dimensions of CHAMPS feasibility within the cultural context of each site while reducing subjectivity and bias in the process of interpretation and reporting. Results: Findings showed that the approach to gain consent to conduct the MITS procedure involves religious factors associated with timing of burial, use of certain terminology, and methods of transporting the body. Community misperceptions and uncertainties resulted in rumor surveillance and consistency in information sharing. Religious pronouncements, recognition of health priorities, attention to pregnancy, and advancement of child health facilitated community acceptability. Conclusions: These findings helped formulate program priorities, guided site-specific adaptations in surveillance procedures, and verified inferences drawn from CHAMPS epidemiological and formative research data. Results informed appropriate community sensitization and engagement activities for introducing and sustaining mortality surveillance, including MITS. Abstract : This article describes a unique qualitative methodology used to determine the feasibility of conducting minimally invasive tissue sampling (MITS) on children <5 years of age. Results contributed to adaptations in surveillance and MITS clinical procedures, and informed essential community sensitization and engagement activities.